Central Pain Sensitization in Patients with Chronic Plaque Psoriasis - Francesco Bellinato; Paolo Gisondi; Angelo Fassio; Giampiero Girolomoni (Adis, Springer Healthcare, 2023)
Abstract Background Central sensitization (CS) is a condition characterized by a disproportionate response to pain stimuli, and is associated with chronic pain conditions such as fibromyalgia, but also with inflammatory arthropathies such as rheumatoid arthritis and psoriatic arthritis (PsA). CS has never been investigated in patients with psoriasis. The aim of this study is to investigate CS in patients with chronic plaque psoriasis. Methods This research involved a cross-sectional observational study of adult patients with moderate-to-severe psoriasis consecutively attending the outpatient clinic of the University Hospital of Verona. Demography, measures of disease severity or activity [i.e., Psoriasis Area and Severity Index (PASI), Disease Activity in Psoriatic Arthritis (DAPSA)], diagnosis of PsA, hypertension, and diabetes were collected. Central Sensitization Inventory (CSI), Dermatology Life Quality Index (DLQI), General Anxiety Disorder-7 (GAD-7), and Patient Health Questionnaire-9 (PHQ-9) were administered. Results A total of 194 patients, including 115 (59%) men, with mean age of 54 ± 13 years, mean PASI of 12.7 ± 6.7, and mean DAPSA of 14.4 ± 3.8 were included. In total, 134 patients (79%) had only psoriasis while 60 (31%) had psoriasis and PsA; 19 (10%) patients had CSI score ≥ 40, which is the threshold for diagnosing CS. The proportion of CS ≥ 40 was higher in patients with PsA compared with psoriasis (17% versus 7%, p = 0.031). The mean CSI score in patients with PsA was higher compared with those with only psoriasis (27.5 ± 13.5 versus 20.7 ± 13.7, p = 0.002). An association between CSI and DLQI [β = 1.25 (95% CI 0.85-1.66)], PASI [β = 1.22 (95% CI 0.74-1.65)], GAD-7 [β = 2.07 (95% CI 1.69-2.45)] and PHQ-9 [β = 2.16 (95% CI 1.76-2.54)] was found independently from age, gender, diabetes, and PsA. Conclusions Central sensitization may be associated with psoriasis, particularly in those with high PASI, concomitant PsA, anxiety, depression, and severe quality of life impairment.